Harnessing cosmic carbon: anaerobic microbial responses to fullerenes under early Earth conditions - Bethune, Elle; Gromov, Andrey; Campbell, Eleanor E. B.; Cockell, Charles S. (Frontiers in Microbiology, 2025)
Fullerenes of extra-terrestrial origin may have been accessible as carbon sources for anaerobic microorganisms on the early Earth. Very little is known about how anaerobic microorganisms respond to and use fullerenes and their soluble derivatives. We present an investigation into the effects of fullerenes C60 and C70 and their hydroxylated fullerol derivatives on an environmentally relevant anaerobic community and a microbial isolate. Fullerenes and fullerols irradiated with 254 nm UV radiation for 2 weeks in the absence of oxygen to simulate UV irradiation under anoxia on early Earth were also assessed. The anaerobic community could grow using glucose in the presence of C60 up to 500 mg/mL without inhibitory effects on growth. Concentrations of C70 of 500 mg/ml were inhibitory. We attribute these results to the different chemical reactivity and photophysical properties of the fullerenes. The experiments suggest the potential for the use of C60 as a sole carbon source. Both C60 and C70 fullerols were inhibitory to growth in the presence of glucose, especially when exposed to light. When we exposed C60 fullerol suspensions to 254 nm UV radiation under an anoxic atmosphere, they become significantly more inhibitory to both the community and the isolate, but only if the cultures are grown under ambient light exposure. The anaerobic isolate was unable to grow on C60 alone, but after UV radiation exposure, the C60 photodegradation products served as a potentially accessible carbon source. Our data show that fullerenes and their derivatives are biologically active and capable of influencing growth in anoxic environments such as those that would have been prevalent on early Earth or in modern-day anoxic soils. Our results show that carbon sources such as these can be both beneficial or deleterious to life depending on their concentrations and environmental processing.